ANALISIS WACANA KRITIS SARA MILLS TENTANG STEREOTIPE PERANAN ISTRI DALAM BERUMAH TANGGA DALAM CERAMAH NASIHAT PERNIKAHAN - Nahartini, Desi; Rasyid, Yumna; Anwar, Miftahulkhairah (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study discusses Sara Mills' critical discourse analysis on stereotypes of the wife's role in the household in the religious speech given at a wedding event. The purpose of this religious speech is to provide understanding to married couples regarding their respective rights and responsibilities, as well as solve problems in the household, and also to prevent and reduce the number of divorce cases. There is a stereotype of women that is synonymous with femininity, namely in the form of the perception that women are attached, that women are gentle, beautiful, easily carried away by emotions, and full of affection. These perceptions of men and women provide cultural assumptions that give different and wider roles to men and make them obtain a relatively high social value status compared to women. In relation to marriage advice lectures, by looking at the stereotype phenomenon that occurs in women, the process and occurrence of marriage advice is one of the important processes and influences the development of these stereotypes. This study uses a qualitative method using the discourse analysis technique of Sara Mills. The primary data was obtained from a long process of repeatedly listening to the marriage advice video lectures to select scenes that display stereotypes towards women in the marriage advice video lectures. The purpose of this study is to find out and analyze critical discourse about the stereotyped role of the wife in marriage in marriage advice lectures.